Filling the Void: Information Seeking and Processing in the Context of Violent Conflicts (Global Media Journal - German Edition, 2023)
This article explores the ways in which violent intergroup conflict affects how people acquire, use, and perceive information. Based on previous studies and empirical findings from field research in four fragile countries (Libya, Sudan, the Democratic Republic of Congo, and Iraq), including qualitative focus group discussions and standardized quantitative surveys, we show that the polarization and instrumentalization of media in these countries produce media skepticism, leading to increased fact-checking and cross-media use among the general public. Uncertainty leads to discussions in the community about what the media presents, indicating that media users try to establish agency through advanced information processing and validation strategies. We posit that this type of media environment facilitates critical media literacy among media-savvy individuals. Moreover, the present study develops a research agenda for analyzing communication and information processing in conflict contexts.
Keywords: fragile statehood; fragmentation; public sphere; media use; violent conflict